Uma proposta de sistema de autoria baseado em plantas baixas para projetar ambientes de realidade virtual: metodologia e estudo de caso aplicados a subestações de energia elétrica - Barreto Junior, Camilo de Lellis (2022)
The application of Virtual Reality (VR) techniques has enhanced numerous engineering processes, benefiting several sectors of the industry. It is widely attributed to user training, prototyping, simulation, architecture, education, and aid tool. It provides a high level of immersion and fidelity in the representation of information. However, the development of VR systems is a complex task, involving teams specialized in low-level code development, 3D modeling and the development of Virtual Environments (VEs) for computer graphics. In view of these adversities, the objective of this study is to present a methodology for designing virtual EPS through an Authoring System (AS) based on Computer-Aided Design (CAD), associated with VR and applied to field asset supervision. The methodology presented provides automatic integration between the floor plan CAD Editor and VR application through a centralized software architecture. The arrangement of architecture components allows editing of VEs, management of the assets, and the use of VR software to take place in parallel and by separate instances in any workplace. Thus, in order for the integration between the components to happen automatically, geometric modeling and CAD symbol conventions were proposed to adapt the virtual assets to the system. The methodology was evaluated by a case study applied in the design of EPS as part of a Research and Development (R&D) project for training and supervision of assets. The results showed parity with the project in a floor plan, evidencing the strategy of integration and reconstruction of the VE. It was possible to analyze the visual credibility in relation to the real and presentation quality of the graphic information. Another considerable result is the accuracy of the Virtual Environment produced by the Authoring System when compared to the manual development process, which showed an error in the positioning of virtual assets when produced manually. Thus, it was possible to obtain greater accuracy with the AS, something important when applied to construction planning, decision-making and simulation.